Anxiety during cancer diagnosis: Examining the influence of monitoring coping style and treatment plan. Issue 2 (26th October 2017) - Bronner, Madelon B.; Nguyen, Minh Hao; Smets, Ellen M.A.; van de Ven, Anthony W.H.; van Weert, Julia C.M.
Abstract: Objective: Studies on anxiety within oncology show a high prevalence of anxiety both during and after the course of the disease. However, little is known about factors that influence the level of anxiety in the diagnostic phase. This study examines the presence of anxiety during diagnosis and treatment planning and explores how a monitoring (ie, information seeking) coping style and the suggested treatment plan (ie, with or without chemotherapy) interact with anxiety. Methods: Anxiety scores (6‐item State‐Trait Anxiety Inventory) were collected from 81 colorectal cancer patients before and after their visit to the outpatient Gastrointestinal Oncological Center Amsterdam. A cut‐off score (>44) was used to indicate highly anxious patients. Results: More than half (59%) of the patients were classified as highly anxious before consultation. Although anxiety scores significantly decreased after consultation ( t  = 3.149, P  = .002), 37% of the patients remained highly anxious. Reductions in anxiety were specifically observed for patients with a higher monitoring coping style and patients for whom a treatment plan without chemotherapy was proposed. Interestingly, high monitors for whom treatment without chemotherapy was proposed showed a major decrease in anxiety, whereas low monitors for whom treatment starting with chemotherapy was proposed showed a great increase in anxiety. Conclusions: The diagnostic phase is associated with high levels of anxiety. Distinct patterns of anxiety were identified, depending on patients' coping style and the suggested treatment plan. Remarkably, patients with a lower monitoring coping style became particularly anxious when they were advised to start treatment with chemotherapy.